A semi-organic antimony fluoride second-order nonlinear optical crystal material and its preparation and application

By developing semi-organic antimony fluorate second-order nonlinear optical crystal material (C5H7N2) (Sb2F7), the problem of lack of high-performance nonlinear optical crystal material suitable for short-wave ultraviolet regions in the prior art is solved, and strong frequency multiplication effect, phase matching and high optical transmittance are achieved, which expands its application prospects in the field of nonlinear optics.

CN118064980BActive Publication Date: 2025-03-21TONGJI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410188428.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-20
Publication Date
2025-03-21
Estimated Expiration
2044-02-20

AI Technical Summary

Technical Problem

The lack of high-performance nonlinear optical crystal materials suitable for short-wave ultraviolet regions in the prior art limits its application in the fields of high-resolution microscopy imaging, precision manufacturing, lithography and optical communication.

Method used

A second-order nonlinear optical crystal material of semiorganoantimony fluorate was developed, with the chemical formula of (C5H7N2) (Sb2F7), which was prepared by hydrothermal reaction and solution volatilization method, with strong powder frequency multiplication effect, phase matching ability, large birefringence and short ultraviolet cut-off edges.

Benefits of technology

The crystal material is doubled by 1064nm laser irradiation and is twice that of KDP crystals, achieving phase matching and has a high optical transmittance in the ultraviolet-visible near-infrared light region, which is suitable for a wide range of applications in the field of nonlinear optics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118064980B_ABST
    Figure CN118064980B_ABST
Patent Text Reader

Abstract

The present invention relates to a semi-organic antimony fluoride second-order nonlinear optical crystal material and its preparation and application. The chemical formula of the material is (C5H7N2)(Sb2F7), which belongs to the monoclinic system, and its space group is Pn (No.7). The unit cell parameters are #imgabs0#α=90°, β=102.44°~102.64°, γ=90°, Z=2, and the unit cell volume is #imgabs1#. Compared with the prior art, the powder frequency doubling effect of the second-order nonlinear optical crystal material (C5H7N2)(Sb2F7) of the present invention under 1064nm laser irradiation is about twice that of KH2PO4 (KDP) crystal, and phase matching can be achieved. In addition, the crystal material has the advantages of a wide light transmission band, stable physical and chemical properties, moderate mechanical hardness, high yield, easy growth, etc., and has important application value in optoelectronic information fields such as laser frequency conversion, optical information storage, and electro-optical modulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nonlinear optical crystal materials, and relates to a semi-organic antimony fluoride second-order nonlinear optical crystal material and a preparation method and application thereof. Background Art

[0002] As a type of optoelectronic functional material, nonlinear optical (NLO) crystal materials with second harmonic generation (SHG) characteristics are widely used in cutting-edge optical and optoelectronic technology fields such as high-resolution microscopy, precision manufacturing, lithography and optical communications. At present, commercial NLO crystal materials are mainly concentrated in the visible and near-infrared regions, such as β-BaB2O4 (BBO), KH2PO4 (KDP), KTiOPO4 (KTP) and LiNbO3 (LN). However, high-performance NLO crystal materials that can be applied to the ultraviolet band are still scarce. Therefore, the development of high-performance NLO crystal materials suitable for the short-wave ultraviolet region has important scientific significance and application value.

[0003] Traditional UV NLO crystals are composed of inorganic functional units, and their optical properties are limited by their inherent composition. Generally speaking, researchers choose alkali metals or alkaline earth metals without dd and ff electronic transitions as A-site cations to ensure that the cutoff edge of the compound will not be red-shifted. However, A-site cations do not contribute to the frequency doubling and birefringence of the crystal, which hinders further improvement of the optical crystal performance. Summary of the invention

[0004] The purpose of the present invention is to provide a semi-organic antimony fluoride second-order nonlinear optical crystal material and its preparation and application. The crystal exhibits a strong powder frequency doubling effect, which is about twice that of KH2PO4 (KDP) crystal, and can achieve phase matching, a large birefringence (0.134@532nm) and a short ultraviolet cutoff edge (275nm). In addition, the crystal has a high yield and is easy to grow, and is a nonlinear optical crystal material with potential application value.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] One of the technical solutions of the present invention provides a semi-organic antimony fluoride second-order nonlinear optical crystal material, whose chemical formula is (C5H7N2)(Sb2F7), belongs to the monoclinic system, its space group is Pn (No.7), and the unit cell parameters are α=90°,β=102.44°~102.64°,γ=90°,Z=2,the unit cell volume is

[0007] The crystal structure of (C5H7N2)(Sb2F7) of the present invention is as follows Figure 1 As shown. The crystal structure of (C5H7N2)(Sb2F7) consists of two-dimensional layers, which are stacked in -AAA- sequence along the a-axis. Layers are composed of organic cations [C5H7N2] + and trans-dimer [Sb2F7] - connected to each other through hydrogen bonds.

[0008] The second technical solution of the present invention provides a method for preparing a semi-organic antimony fluoride second-order nonlinear optical crystal material, comprising the following steps:

[0009] (1) mixing an organic source, an antimony source, a fluorine source and water to form an initial mixed raw material, placing the mixed raw material in a closed hydrothermal reactor, heating and crystallizing the mixed raw material, cooling the mixed raw material to room temperature, and obtaining a clear and transparent solution;

[0010] (2) The obtained solution is evaporated at room temperature to obtain colorless transparent crystals, which are the target product.

[0011] Furthermore, the organic source is 4-aminopyridine.

[0012] Furthermore, the antimony source is antimony trioxide.

[0013] Furthermore, the fluorine source is hydrofluoric acid.

[0014] Furthermore, the amount of organic source, antimony source, fluorine source and water added to the initial mixed raw material satisfies: the molar ratio of organic source, antimony element, fluorine element and water is (1-10):(1-10):(1-40):(0-100). Preferably, it is (1-10):(1-10):(1-20):(0-40). Preferably, the amount of water added is not 0.

[0015] Further, the temperature of the heating crystallization is 70-100° C., and the crystallization time is not less than 24 hours. More preferably, the temperature of the heating crystallization is 90-100° C., and the crystallization time is not less than 48 hours.

[0016] Furthermore, the cooling rate is 0.5 to 15°C / h. Preferably, the cooling rate is 0.5 to 5°C / h.

[0017] Furthermore, the volatilization time at room temperature is not less than one week, and more preferably, the volatilization time at room temperature is not less than two weeks.

[0018] A third technical solution of the present invention provides an application of a semi-organic antimony fluoride second-order nonlinear optical crystal material in a laser frequency converter, an optical parametric oscillator, an optical parametric amplifier and a photoelectric rectifier.

[0019] Furthermore, the second-order nonlinear optical crystal material is used in a laser frequency converter to output 532nm laser under 1064nm laser irradiation.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] (1) The present application provides a new second-order nonlinear optical crystal (C5H7N2)(Sb2F7), the frequency doubling intensity of which is twice that of KDP crystal under 1064nm laser irradiation, and phase matching can be achieved. In addition, the crystal material has high optical transmittance in the ultraviolet, visible and near-infrared light regions, its ultraviolet absorption cutoff edge is 275nm, and its thermal decomposition temperature is 200℃. The crystal material has broad application prospects in the field of nonlinear optics.

[0022] (2) The present application also provides a method for preparing a second-order nonlinear optical crystal (C5H7N2)(Sb2F7), and a colorless (C5H7N2)(Sb2F7) crystal is prepared by a two-step method of hydrothermal and solution volatilization. The synthesis method is convenient, the synthesis conditions are mild, the yield is high, and the growth is easy, and it is easy to obtain a millimeter-level single crystal with high optical quality and high purity. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the crystal structure of (C5H7N2)(Sb2F7);

[0024] Figure 2 This is a crystal photograph of (C5H7N2)(Sb2F7);

[0025] Figure 3 The X-ray diffraction pattern of sample 1# obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is compared with the pattern obtained by X-ray diffraction test after sample 1# is ground into powder and the pattern obtained by X-ray diffraction test after being exposed to air for one month;

[0026] Figure 4 is the UV-Vis-NIR transmission spectrum of sample 1#;

[0027] Figure 5 is the infrared spectrum of sample 1#;

[0028] Figure 6 This is the thermogravimetric analysis spectrum of sample 1#;

[0029] Figure 7 It is the second harmonic signal diagram of sample 1# and standard KDP sample with the sample size ranging from 150 to 200 μm;

[0030] Figure 8This is the second harmonic phase matching diagram of sample 1# in the 1064nm band. DETAILED DESCRIPTION

[0031] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0032] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0033] Embodiment 1:

[0034] Preparation of samples 1# to 6#

[0035] An organic source (i.e. 4-aminopyridine), an antimony source (i.e. antimony trioxide), a fluorine source (i.e. 40 wt% hydrofluoric acid) and water are mixed in a certain proportion to form a starting material, placed in a closed hydrothermal reactor, heated for crystallization, cooled to room temperature, and a clear and transparent solution is obtained; the obtained solution is slowly evaporated at room temperature to obtain a colorless and transparent (C5H7N2)(Sb2F7) crystal, such as Figure 2 The yield of (C5H7N2)(Sb2F7) crystals was 85% (calculated based on Sb).

[0036] The relationship between the types and proportions of raw materials in the initial mixture, crystallization temperature, crystallization and volatilization time and sample number is shown in Table 1.

[0037] Table 1 Correspondence between samples, raw materials and synthesis conditions

[0038]

[0039] Embodiment 2:

[0040] Crystal structure analysis of samples 1# to 6#

[0041] The structures of samples 1# to 6# were analyzed using single crystal X-ray diffraction and powder X-ray diffraction methods.

[0042] The single crystal X-ray diffraction test was carried out on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The data collection temperature was 100K, and the diffraction light source was graphite monochromatized Mo-Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the Olex2 program package; the positions of heavy atoms were determined using the direct method, and the coordinates of the remaining atoms were obtained using the difference Fourier synthesis method; the F-based 2The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.

[0043] The powder X-ray diffraction test was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu-Kα, a wavelength The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 10-70°, and the scanning step is 0.02°.

[0044] Among them, the single crystal X-ray diffraction results show that samples 1#~6# have the same chemical formula and crystal structure, the chemical formula is (C5H7N2)(Sb2F7), crystallized in the monoclinic system, the space group is Pn, and the unit cell parameters are α=90°,β=102.44°~102.64°,γ=90°,Z=2,the unit cell volume is

[0045] Take sample 1# as a typical example, its crystal structure data is α=90°,β=102.5420°,γ=90°,Z=2,the unit cell volume is Its crystal structure is Figure 1 shown.

[0046] The powder X-ray diffraction test results show that in the XRD spectra of samples 1# to 6#, the positions of the sample diffraction peaks and the diffraction peaks fitted by the single crystal data are the same.

[0047] Take sample 1# as a typical example. Figure 3 As shown in the figure, the X-ray diffraction pattern obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is consistent with the peak position and peak intensity of the pattern obtained by X-ray diffraction test after sample 1# is ground into powder, indicating that the obtained sample has high purity. After being exposed to air for one month, no obvious impurity peaks were observed in the powder X-ray diffraction pattern of sample 1# crystal compared with the previous one, indicating that the (C5H7N2)(Sb2F7) crystal has good chemical stability.

[0048] Embodiment 3:

[0049] UV-Vis-NIR transmission spectrum test

[0050] The UV-Vis-NIR transmission spectrum test of sample 1# was conducted on a Carry 5000 UV-Vis-NIR spectrophotometer from Agilent Technologies, USA. Figure 4 As shown by Figure 4It can be seen that the compound has no obvious absorption peak from 275nm to 2000nm, which proves that the compound has a wide optical transmission range and an optical band gap of 4.51eV.

[0051] Embodiment 4:

[0052] Infrared spectrum test

[0053] The infrared spectrum test of sample 1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Figure 5 As shown, the characteristic absorption peaks in the infrared spectrum indicate the presence of 4-aminopyridine groups and Sb-F bonds in the sample.

[0054] Embodiment 5:

[0055] Thermogravimetric testing

[0056] The thermogravimetric test of sample 1# was conducted on a Netzsch STA 409PC thermogravimetric analyzer manufactured by Netzsch Equipment Manufacturing Co., Ltd., Germany. The results are shown in the figure below. Figure 6 As shown by Figure 6 It can be seen that the compound can be stable to 200°C and has good thermal stability.

[0057] Embodiment 6:

[0058] Frequency doubling test experiment and results

[0059] The frequency doubling test experiment of sample 1# is as follows: a Radiant Tunable Laser System (Amplitude, Horizon II Mid-band Optical Parametric Oscillator; 5Hz) is used to generate a laser with a wavelength of 1064nm and use it as the fundamental frequency light to irradiate the tested crystal powder, and the intensity of the second harmonic is detected by using Ocean Optics Maya2000Pro spectrometer. The crystal sample and the standard sample KDP crystal are ground separately, and crystals of different particle sizes are sieved out with a standard sieve, and the particle size ranges are 26-50, 50-74, 74-105, 105-150, 150-200, and 200-280μm. The change law of the frequency doubling signal with the particle size is observed to determine whether it can achieve phase matching. Under the same test conditions, the second harmonic intensity generated by the sample and the standard sample KDP is compared to obtain the relative size of the sample frequency doubling effect.

[0060] The test results show that the compound (C5H7N2)(Sb2F7) has a strong powder frequency-doubled effect. Under 1064nm wavelength laser irradiation, the frequency-doubled signal intensity is twice that of KDP crystal (such as Figure 7). The crystal material can achieve phase matching under 1064nm laser irradiation (such as Figure 8 ).

[0061] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A semi-organic antimony fluoride second-order nonlinear optical crystal material, characterized in that: Its chemical formula is (C5H7N2)(Sb2F7), it belongs to the monoclinic system, its space group is Pn(No.7), and its unit cell parameters are α=90°,β=102.44°~102.64°,γ=90°,Z=2,the unit cell volume is 2. The method for preparing a semi-organic antimony fluoride second-order nonlinear optical crystal material according to claim 1, characterized in that: The following steps are involved: (1) mixing an organic source, an antimony source, a fluorine source and water to form an initial mixed raw material, placing the mixture in a closed hydrothermal reactor, heating and crystallizing the mixture, cooling the mixture to room temperature, and obtaining a clear and transparent solution; (2) volatilizing the obtained solution at room temperature to obtain colorless transparent crystals, which are the target product; The organic source is 4-aminopyridine; The antimony source is antimony trioxide; The fluorine source is hydrofluoric acid; The amounts of the organic source, antimony source, fluorine source and water added to the initial mixed raw material satisfy the following molar ratio of the organic source, antimony element, fluorine element and water: (1-10): (1-10): (1-40): (0-100); The temperature of heating crystallization is 70-100°C, and the crystallization time is not less than 24h.

3. The method for preparing a semi-organic antimony fluoride second-order nonlinear optical crystal material according to claim 2, characterized in that: The cooling rate is 0.5~15℃ / h; The evaporation time at room temperature is not less than one week.

4. Application of the semi-organic antimony fluoride second-order nonlinear optical crystal material as claimed in claim 1 in laser frequency converters, optical parametric oscillators, optical parametric amplifiers and photoelectric rectifiers.

5. The use of a semi-organic antimony fluoride second-order nonlinear optical crystal material according to claim 4, characterized in that: The second-order nonlinear optical crystal material is used in a laser frequency converter, which outputs a 532nm laser under 1064nm laser irradiation.

Citation Information

Patent Citations

  • Organic hybrid thioantimonate frequency-doubling crystal material and preparation and application thereof

    CN110055592A

  • Near-ultraviolet nonlinear optical crystal rubidium antimony fluoride selenate and preparation method and application thereof

    CN114059167A